Association between serum osmolality and 28-day all-cause mortality in patients with heart failure and reduced ejection fraction: a retrospective cohort study from the MIMIC-IV database - Zou, Qi; Li, Jiazheng; Lin, Pengyang; Ma, Jialiang; Wei, Zhiliang; Tao, Ting; Han, Guodong; Sun, Shougang (Frontiers in Endocrinology, 2024)
Background: Previous studies have not thoroughly explored the impact of serum osmolality levels on early mortality in heart failure and reduced ejection fraction (HFrEF) patients. The purpose of this study was to investigate the relationship between serum osmolality levels and early all-cause mortality in patients with HFrEF.The open access MIMIC-IV database was the source of data for our study. We collected demographic data, vital signs, laboratory parameters, and comorbidities of the included patients and divided them into 3 groups based on their initial serum osmolality on admission, with the primary outcome being all-cause mortality within 28 days of admission, constructing Cox proportional risk analysis, Smoothing Spline Fitting Curve, the Kaplan-Meier survival curve were used to assess the relationship between serum osmolality and early mortality in HFrEF patients.Results: A total of 6228 patients (55.31% male) were included. All-cause mortality within 28 days on admission was 18.88% in all patients. After adjusting for confounders, higher serum osmolality levels were independently associated with an increased risk of 28-days all-cause mortality compared with the reference group (Reference group Q2: 290-309 mmol/L, Q4: HR, 1.82 [95% CI 1.19-2.78] P<0.05, Q5: HR, 1.99 [95% CI 1.02-3.91] P<0.05). Smooth spline fitting revealed a U-shaped association between serum osmolality and 28-days all-cause mortality. Further threshold effect analysis results suggested that each unit increase in serum osmolality level was associated with a 2% increase in 28-days all-cause mortality when serum osmolality levels were ≥ 298.8 mmol/L (HR, 1.019 [95% CI 1.012-1.025] P<0.05).A U-shaped correlation between initial serum osmolality and 28-days all-cause mortality in HFrEF patients was identified, revealing higher osmolality levels significantly increase mortality risk. These results underscore serum osmolality's critical role in early mortality among HFrEF patients, highlighting the need for further, larger-scale studies for validation.